First‐trimester screening for pre‐eclampsia and small for gestational age: A comparison of the gaussian and Fetal Medicine Foundation algorithms. Issue 1 (11th July 2022) - Serrano, Berta; Bonacina, Erika; Rodo, Carlota; Garcia‐Manau, Pablo; Sanchez‐Duran, María Ángeles; Pancorbo, María; Forcada, Cristina; Murcia, María Teresa; Perestelo, Ana; Armengol‐Alsina, Mireia; Mendoza, Manel; Carreras, Elena
Abstract: Objective: Pre‐eclampsia (PE) and small for gestational age (SGA) can be predicted from the first trimester. The most widely used algorithm worldwide is the Fetal Medicine Foundation (FMF) algorithm. The recently described Gaussian algorithm has reported excellent results although it is unlikely to be externally validated. Therefore, as an alternative approach, we compared the predictive accuracy for PE and SGA of the Gaussian and FMF algorithms. Methods: Secondary analysis of a prospective cohort study was conducted at Vall d'Hebron University Hospital (Barcelona) with 2641 singleton pregnancies. The areas under the curve for the predictive performance for early‐onset and preterm PE and early‐onset and preterm SGA were calculated with the Gaussian and FMF algorithms and subsequently compared. Results: The FMF and Gaussian algorithms showed a similar predictive performance for most outcomes and marker combinations. Nevertheless, significant differences for early‐onset PE prediction favored the Gaussian algorithm in the following combinations: mean arterial blood pressure (MAP) with pregnancy‐associated plasma protein A, MAP with placental growth factor, and MAP alone. Conclusions: The first‐trimester Gaussian and FMF algorithms have similar performances for PE and SGA prediction when applied with all markers within a routine care setting in a Spanish population, adding evidence to the external validity of the FMF algorithm. Synopsis: The first‐trimester Gaussian and Fetal Medicine Foundation algorithms have similar predictive performances for pre‐eclampsia and small‐for‐gestational‐age fetuses.